Paraguay Jobs Diagnostic : The Dynamic Transformation of Employment - Ruppert Bulmer, Elizabeth N.; Watson, Samantha Maria; De Padua, David Keith Santos (World Bank, Washington, DC, 2017)
Paraguay in the last decade and a half not only experienced robust economic growth and improved labor outcomes across sectors, it also saw marked improvements in job quality and the creation of many new jobs that are good for development. Good jobs for development, the focus of this analysis, are those that boost living standards, have higher levels of productivity, and enhance social cohesion through positive social externalities. The analysis in this report describes the ways in which employment outcomes have improved for a majority of Paraguayans, the degree to which certain types of workers have not benefited from ongoing dynamic transformations, and the challenges for sustaining and enhancing labor market gains in the future.